Post-SELEX modification of aptamers through reversible formation of N-methoxy-1,3-oxazinane (MOANA) nucleoside analogues - Herath, Muditha (My University, 2024)
The effective use of aptamers has been developed significantly in the recent past due to their widespread applications in areas such as therapeutics, biosensors and nanotechnological applications. Due to this increasing demand, researchers are continuously engaged in modifying aptamers to ensure a strong and selective binding with the targets. Apart from the general SELEX method, post-SELEX modifications have become more efficient to develop aptamer libraries which can efficiently bind with the target. Out of the different types of aptamers which can be further modified, the “cocaine binding aptamer” (MN4) can be identified as a prominent candidate. Even though MN4 was originally developed to bind with cocaine, it has a higher affinity towards the “off-target” quinine. Therefore, quinine was used as the target ligand in this project. Previous studies have reported several investigations on binding of different quinine derivatives to the cocaine aptamer. However, there is no literature on screening for aptamer-aldehyde combinations with improved binding affinity for quinine. In this work, the effect of modifications at the binding site on the binding affinity of MN4 was examined. By replacing any of the three pre-determined nucleotides of the aptamer by benzylidene protected (2R,3S)-4-(methoxyamino)butane-1,2,3-triol phosphoramidite (a MOANA residue), three different modified aptamers (T19, C20 and A21) were synthesized. Further elaboration was carried out by reacting the aptamers with selected mixtures of aldehydes, in the presence and absence of quinine. The reaction was carried out at pH 5.5 and room temperature to promote reversible formation of respective MOANA analogues. Further analysis by UHPLC/MS showed promising results for the C20 scaffold with methyl-4-formylbenzoate and 3-nitrobenzaldehyde derivatives.
Keywords: aptamers, post-SELEX modifications,1,3-oxazinanes, derivatization